Rethinking dosimeter assignment for military radiation safety - Hosub Chi; Jungmi Park; Gyoungjun Choi; Kang Ku (선진국방연구)
The increasing use of portable X-ray generators in military operations—particularly for explosive detection and counter-terrorism—has highlighted the need for a radiation safety strategy tailored to field-based, low-dose environments. This study evaluates the performance of thermoluminescent dosimeters (TLDs) and electronic personal dosimeters (EPDs) under controlled pulsed X-ray conditions using the XRS-3 generator, focusing on their sensitivity, dose-response characteristics, and operational suitability in military contexts. The results showed that while TLDs exhibited high accuracy in cumulative dose tracking, they failed to detect radiation beyond 3 meters or at low pulse counts. In contrast, EPDs—although they showed some inconsistencies in cumulative dose measurements under low-dose conditions—successfully detected radiation at all distances and pulse settings. Their ability to provide immediate feedback and detect fluctuations in real time makes them more suitable for dynamic radiation monitoring in military field environments. The study provides a solid foundation for revising current military dosimetry protocols in current military radiation safety management practices.